Combination of Probiotics and Sublingual Immunotherapy in Allergic Rhinitis: A Real-Life Study - Renato Rossi,; Lucilla Rossi ,; Giorgio Monasterolo, (Journal of Pharmacy and Nutrition Sciences, 2016)
Probiotics are increasingly recognized as capable of modulating immune responses. Some probiotic strains show the potential of inducing a different lymphocyte polarization, promoting the Th1 phenotype and inhibiting, at the same time, the allergy-prone Th2 phenotype. On this basis, we could expect that probiotics may act synergistically to improve the clinical efficacy of sublingual allergen immunotherapy (SLIT). In this study, 30 patients affected by allergic rhinitis undergoing SLIT, were concomitantly administered a probiotic supplement (n = 14) or not (n = 16), according to their preference. Nasal symptom score, rescue medication score and ‘well-days’ were evaluated after 2 and 4 months of treatment. Patients who were administered SLIT plus probiotics showed a trend toward reduction of the nasal symptoms (-7.1%, p = ns) with a significant reduction of medication score (-32.6, p = 0.02) and an increase of ‘well-days’ (35.1, p = 0.02). These preliminary data, from a small study population, suggest that this combined approach with SLIT and probiotics could result in an increased efficacy of the SLIT treatment.